Multivariate data analysis for finding the relevant fatty acids contributing to the melting fractions of cream1. (8th November 2012) - Buldo, Patrizia; Larsen, Mette K; Wiking, Lars
Abstract Background The melting behaviour and fatty acid composition of cream from a total of 33 cows from four farms were analysed. Multivariate data analysis was used to identify the fatty acids that contributed most to the melting points and to differentiate between creams from different practical feeding regimes. Results It was demonstrated that the melting point of the medium melting fraction of milk fat was positively correlated with palmitic acid (C16:0), whereas it was negatively correlated with oleic acid (C18:1 cis9), conjugated linoleic acid (CLA cis9 trans11), vaccenic acid (C18:1 trans11), elaic acid (C18:1 trans9) and myristoleic acid (C14:1). The melting points of the high melting fractions could not be related to the fatty acid composition. Addition of palmitic acid‐based fat supplement to the feeding ration in combination with a lower forage intake increased the amount of C16:0 and palmitoleic acid (C16:1) in milk fat, whereas it decreased the amount of stearic acid (C18:0) and C18:1 trans fatty acid. Average data on the melting behaviour of cream separated the farms into two groups where the main differences in feeding were the amounts of maize silage and rapeseed cake used. Conclusion Multivariate analysis of data from individual cows identified the most relevant fatty acids contributing to the melting point of the medium melting fraction of cream. The fatty acid composition of milk fat could differentiate cream from different feeding strategies; however, owing to individual cow variation, it was not possible to extract clear correlations between feeding regime and melting behaviour of cream.